2014
DOI: 10.3201/eid2004.130517
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Clade 2.3.2.1 Avian Influenza A(H5N1) Viruses, Indonesia, 2012

Abstract: After reports of unusually high mortality rates among ducks on farms in Java Island, Indonesia, in September 2012, influenza A(H5N1) viruses were detected and characterized. Sequence analyses revealed all genes clustered with contemporary clade 2.3.2.1 viruses, rather than enzootic clade 2.1.3 viruses, indicating the introduction of an exotic H5N1 clade into Indonesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 10 publications
1
39
0
2
Order By: Relevance
“…In addition, Figure S4 has shown that a new clade was found in 2012 among ducks. Even though the newer clade was found to be slight different than the previously found clade in Indonesia (Dharmayanti et al, 2014), the virus follow similar molecular clock as the previous clade (Figure 3). The difference might be caused by antigenic drift that can occur over time (Hartaningsih et al, 2015).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In addition, Figure S4 has shown that a new clade was found in 2012 among ducks. Even though the newer clade was found to be slight different than the previously found clade in Indonesia (Dharmayanti et al, 2014), the virus follow similar molecular clock as the previous clade (Figure 3). The difference might be caused by antigenic drift that can occur over time (Hartaningsih et al, 2015).…”
Section: Discussionsupporting
confidence: 58%
“…However, the genetic diversity increased again after 2012. In 2012, several studies mentioned the introduction of a new HPAI H5N1 clade that has never been found previously in Indonesia (Dharmayanti et al, 2014). In fact, this new clade has raised the possibility of multiple introductions into Indonesia (Dharmayanti et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Nine flocks (75%) had recently been HPAI H5N1‐vaccinated a median of 3 days [IQR 2–5] prior to onset of clinical signs (Table ). The reported mortality (16.0%) was lower compared with that observed in 2.3.2.1 clade outbreaks in India, Bangladesh and Indonesia (>60%) (Nagarajan et al., ; Dharmayanti et al., ; Haider et al., ). In our study farms, the variable mortality was statistically correlated with the length of time between onset of signs and farm visit (Pearson's correlation = 0.61, P = 0.01) (data not shown).…”
Section: Resultsmentioning
confidence: 80%
“…Until December 2008, Sukabumi and Cianjur were the districts with the highest cases of H5N1 in West Java, and West Java was the province with the highest number of H5N1 outbreaks in Indonesia (Yupiana et al 2010 (Dharmayanti et al 2014). However, this new clade H5N1 caused disease and mortalities mostly in ducks, whereas poultry including, native chicken, apparently were not affected (Empres 2014).…”
Section: Discussionmentioning
confidence: 99%